CO/O(2) assisted oxidative carbon–carbon and carbon–heteroatom bond cleavage for the synthesis of oxosulfonates from DMSO and olefins - Shao, Ailong (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
Selective carbon–carbon and carbon–heteroatom bond cleavage was achieved in a one reaction system. With this strategy a novel Pd/Cu-catalyzed aerobic oxidative oxosulfonation of olefins with DMSO has been developed. Preliminary mechanistic investigations indicated that CO/O(2) assisted the bond cleavage and the leaving groups from the starting materials were trapped by O(2) and underwent a hydroxylation process.